Cohort profile: The Observational cohort for the study of DOlutegravir in Antiretroviral Combination REgimens (ODOACRE). Issue 12 (2nd December 2019) - Ciccullo, Arturo; Baldin, Gianmaria; Capetti, Amedeo; Borghi, Vanni; Sterrantino, Gaetana; Latini, Alessandra; Madeddu, Giordano; Celani, Luigi; Vignale, Francesca; Rossetti, Barbara; Dusina, Alex; Cossu, Maria Vittoria; et al.
Abstract : Purpose: The Observational cohort for the study of DOlutegravir in Antiretroviral Combination REgimens (ODOACRE) cohort was established in Italy in 2016 to evaluate the overall efficacy and tolerability of dolutegravir (DTG)-based antiretroviral (ARV) regimens in clinical practice. Participants: The ODOACRE cohort enrols all adult HIV-1-infected patients, both treatment-naïve and treatment-experienced, starting a DTG-based ARV regimen, in 11 clinical centres in Italy from 2014. Findings to date: In recent years, various works by the ODOACRE cohort have been produced, demonstrating the high efficacy and tolerability of DTG-based ARV regimens in clinical practice, both in ART-naïve (in the setting of acute HIV-1 infection and late presenters patient) and experienced patients. We confirmed the virological efficacy of DTG-based regimens and we evaluated predictors of virological failure. We investigated cause of discontinuation and evaluated tolerability and metabolic profile of the regimens. Within these investigations, we explored particularly the use of DTG in simplification in two-drug regimen with either rilpivirine or lamivudine. We also compared DTG-based regimens with other integrase inhibitors in clinical practice. Future plans: To continue to study long-term efficacy and tolerability of DTG-based regimens is the purpose of the ODOACRE cohort.